2022
DOI: 10.7759/cureus.24764
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of LigaSure in Laparoscopic Sutureless Appendectomy

Abstract: Background The closure of the appendiceal stump is a crucial step during an appendectomy. The purpose of this study is to evaluate the LigaSure Vessel Sealing System in laparoscopic appendectomy (LA) for sealing and dividing the base of the appendix. Material and methods Laparoscopic appendectomy was performed using the 5-mm LigaSure Vessel Sealer in 53 patients, and the mesoappendix along with the base of the appendix was divided by LigaSure. Patient demographic details, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Thanks to the data obtained from these studies, there have been studies in human studies demonstrating that the use of LigaSure is safe for the closure of appendix stump in pediatric and adult age groups. 13,14 Since there is no study comparing the use of LigaSure with other methods for the closure of the appendix stump in humans, this study is a pioneering study in this regard. Our study did not find a difference between the use of hemoclip or LigaSure as the method of closing the appendix stump, which applied to similar groups, in terms of safety and complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the data obtained from these studies, there have been studies in human studies demonstrating that the use of LigaSure is safe for the closure of appendix stump in pediatric and adult age groups. 13,14 Since there is no study comparing the use of LigaSure with other methods for the closure of the appendix stump in humans, this study is a pioneering study in this regard. Our study did not find a difference between the use of hemoclip or LigaSure as the method of closing the appendix stump, which applied to similar groups, in terms of safety and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the data obtained from these studies, there have been studies in human studies demonstrating that the use of LigaSure is safe for the closure of appendix stump in pediatric and adult age groups. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [ 38 ] reported a series of 53 patients aged between 11 and 60 years with a successful appendectomy using a 5 mm LigaSure TM instrument that was repeatedly applied to obtain a resection. This also supports our findings, namely, that the 5 mm instrument achieves resection after repeated application.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of the LVSS in the division of the mesoappendix during laparoscopic appendectomy has been reported by both Aydogan et al [ 35 ] and Sucullu et al [ 36 ] in a series of 127 and 32 cases, respectively, with good results. Transection of the apex ceaci is mainly reported in animal models [ 37 ]; conversely, Gupta et al [ 38 ] reported a series of 53 patients with successful appendectomies using a 5 mm LigaSure TM instrument.…”
Section: Introductionmentioning
confidence: 99%
“…The most crucial step in this operation is to seal the appendiceal stump securely, that is why research on the subject is still being done [7]. The base of the appendix can be secured using a variety of techniques, including energy-based devices, metallic or plastic clips, staplers, or suture materials (extracorporeal or intracorporeal) [8]. All method has advantages and disadvantages of their own.…”
Section: Introductionmentioning
confidence: 99%